Markups, Quality, and Trade Costs - Natalie Chen; Luciana Juvenal (Center for Economic Studies and ifo Institute (CESifo), 2019)
We investigate theoretically and empirically how exporters adjust their markups across destinations depending on bilateral distance, tariffs, and the quality of their exports. Under the assumption that trade costs are both ad valorem and per unit, our model predicts that markups rise with distance and fall with tariffs, but these effects are heterogeneous and are smaller in magnitude for higher quality exports. We find strong support for the predictions of the model using a unique data set of Argentinean firm-level wine exports combined with experts wine ratings as a measure of quality.
Keywords: F12; F14; F31; 330; distance; export unit values; heterogeneity; markups; quality; tariffs; trade costs; wine